Monetary Union: European Lessons, Latin American Prospects - Eduard Hochreiter; Klaus Schmidt-Hebbel; Georg Winckler (Oesterreichische Nationalbank (OeNB), 2002)
In this paper selective issues of long-run sustainability of monetary unions are analyzed. Using theoretical insights and the experience of EMU up to now we argue that empirical evidence on OCA criteria for EMU suggests that benefits for the countries participating in EMU outweigh costs by a relatively large margin although by varying degrees from country to country. Fiscal policy rules are necessary for EMU to succeed. We also conclude that EMU has been driven by political considerations. A sound financial sector is a precondition. With regard to lessons to be drawn for Latin America and the Caribbean we first find that there has been a strong push towards the floating cum inflation-targeting corner and to regional trade integration. Moreover, it seems that, in contrast to EMU, the benefit-cost balance of a move to monetary union is much less favorable in Latin America and the Caribbean and, most important, the political dimension missing.
Keywords: E42; E52; E58; F33; 330; Exchange rate regimes; Monetary Union; Transition; Emerging Market Economies